2022
DOI: 10.3390/cimb44110381
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of the NAC Gene Family in Kandelia obovata, a Typical Mangrove Plant

Abstract: The NAC (NAM, ATAF1/2, and CUC2) gene family, one of the largest transcription factor families in plants, acts as positive or negative regulators in plant response and adaption to various environmental stresses, including cold stress. Multiple reports on the functional characterization of NAC genes in Arabidopsis thaliana and other plants are available. However, the function of the NAC genes in the typical woody mangrove (Kandelia obovata) remains poorly understood. Here, a comprehensive analysis of NAC genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…These results suggested that members of the CmNAC gene family were closely related to the growth and development of chestnut. Additionally, a large number of cis -acting elements related to plant resistance to stress were identified, such as wound-responsive elements, cis -acting elements involved in defense and stress responsiveness ( Figure 4 ; Supplementary Table S4 ) ( Sun et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that members of the CmNAC gene family were closely related to the growth and development of chestnut. Additionally, a large number of cis -acting elements related to plant resistance to stress were identified, such as wound-responsive elements, cis -acting elements involved in defense and stress responsiveness ( Figure 4 ; Supplementary Table S4 ) ( Sun et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis based on KaKs calculations reveals that all duplicate gene pairs evolved under purifying selection, indicating that A. mongolicus has become well adapted to extreme environments of cold and drought through long-term evolution. Phylogenetic analysis showed that AmNACs are divided into 15 groups, which is like the NAC family in Isatis indigotica [62], but different from Kandelia bovate (16 groups) [64] and Dimocarpus longan (14 groups) [65]. The NAC family is categorized into three subfamilies: NAM, ATAF, and CUC.…”
Section: Discussionmentioning
confidence: 99%
“…The ABI PRISM 7500 Real-time PCR Systems, manufactured by Applied Biosystems, were utilized in this study to perform quantitative real-time PCR (qRT-PCR) assays. The 2 −∆∆CT approach, as previously outlined ( Hussain et al., 2022c ; Sun et al., 2022 ), was employed for data analysis. The actin gene of Kandelia obovata (KoActin) was used as a reference gene using the sequence given by Sun et al., 2022 (forward primer: CAATGCAGCAGTTGAAGGAA, reverse primer: CTGCTGGAAGGAACCAAGAG).…”
Section: Methodsmentioning
confidence: 99%
“…The 2 −∆∆CT approach, as previously outlined ( Hussain et al., 2022c ; Sun et al., 2022 ), was employed for data analysis. The actin gene of Kandelia obovata (KoActin) was used as a reference gene using the sequence given by Sun et al., 2022 (forward primer: CAATGCAGCAGTTGAAGGAA, reverse primer: CTGCTGGAAGGAACCAAGAG). The KoNRAMPs gene primers utilized in real-time PCR are listed in Table 1 and were created with the PRIMER 5.0 software ( http://www.premierbiosoft.com ) ( Hussain et al., 2023 ).…”
Section: Methodsmentioning
confidence: 99%